Use of iodine to biofortify and promote growth and stress tolerance in crops - Medrano Macías, Julia Rosa; Leija Martínez, Paola; González Morales, Susana; Juárez Maldonado, Antonio; Benavides Mendoza, Adalberto (2016)
odine is not considered essential for land plants; however, in some aquatic plants, iodine plays a critical role in antioxidant metabolism. In humans, iodine is essential for the metabolism of the thyroid and for the development of cognitive abilities, and it is associated with lower risks of developing certain types of cancer. Therefore, great efforts are made to ensure the proper intake of iodine to the population, for example, the iodization of table salt. In the same way, as an alternative, the use of different iodine fertilization techniques to biofortify crops is considered an adequate iodine supply method. Hence, biofortification with iodine is an active area of research, with highly relevant results. The agricultural application of iodine to enhance growth, environmental adaptation, and stress tolerance in plants has not been well explored, although it may lead to the increased use of this element in agricultural practice and thus contribute to the biofortification of crops. This review systematically presents the results published on the application of iodine in agriculture, considering different environmental conditions and farming systems in various species and varying concentrations of the element, its chemical forms, and its application method. Some studies report beneficial effects of iodine, including better growth, and changes in the tolerance to stress and antioxidant capacity, while other studies report that the applications of iodine cause no response or even have adverse effects. We suggested different assumptions that attempt to explain these conflicting results, considering the possible interaction of iodine with other trace elements, as well as the different physicochemical and biogeochemical conditions that give rise to the distinct availability and the volatilization of the element.